Analyzing trophic ecosystem functions with the interaction functional space. (May 2023) - Bello, Carolina; Schleuning, Matthias; Graham, Catherine H.
Highlights: Trophic ecosystem functions between consumer and resource species have been explored either using functional trait diversity or interaction networks. However, these approaches miss a critical element that has not been addressed yet: traits only impact trophic ecosystem functions when species interact. Understanding the mechanisms shaping trophic ecosystem functions requires the integration of functional and network ecology into a single trait-based framework. Based on previous developments of functional diversity and interactions networks, we present the interaction functional space (IFS) as an integrative framework to analyze how the traits of interacting species build up a combined functional space that underpins trophic ecosystem functions. The IFS can be applied to a broad range of trophic functions to understand how they emerge and change under global change. Abstract: Quantifying the vulnerability of ecosystems to global change requires a better understanding of how trophic ecosystem functions emerge. So far, trophic ecosystem functions have been studied from the perspective of either functional diversity or network ecology. To integrate these two perspectives, we propose the interaction functional space (IFS) a conceptual framework to simultaneously analyze the effects of traits and interactions on trophic functions. We exemplify the added value of our framework for seed dispersal and wood decomposition and show how species interactions influence the relationship between functional trait diversity and trophic functions. We propose future applications for a range of functions where the IFS can help to elucidate mechanisms underpinning trophic functions and facilitate understanding of functional changes in ecosystems amidst global change.